2017
DOI: 10.4236/ajibm.2017.75051
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Price Fairness in Pay-What-You-Want: A Multi-Country Study

Abstract: The present study investigated perceived price fairness (PPF) and aimed to reveal determinants of PPF within the participative pricing mechanism paywhat-you-want (PWYW). Results support the hypothesis that PPF in PWYW conditions is higher than PPF in ordinary price setting (OPS) conditions. Determinants of PPF in PWYW conditions were identified to include both the price level and the degree of social interaction. Whereas the results conform to previous research that PPF correlates negatively with the price lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…In this regard, the present work provides evidence of how some contextual factors in the implementation of PWYW may affect consumers' behavior and hence the experience's profitability. A case‐study approach is relevant to the topic because the scarce works on PWYW from a cross‐country approach have found significant differences between countries (see Bettray et al ., 2017; Dorn and Suessmair, 2017). Therefore, the article contributes to the literature on PWYW and non‐conventional pricing strategies by clarifying the role of different motivations in consumers' economic decisions, and by identifying contextual factors that trigger or inhibit non‐selfish behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the present work provides evidence of how some contextual factors in the implementation of PWYW may affect consumers' behavior and hence the experience's profitability. A case‐study approach is relevant to the topic because the scarce works on PWYW from a cross‐country approach have found significant differences between countries (see Bettray et al ., 2017; Dorn and Suessmair, 2017). Therefore, the article contributes to the literature on PWYW and non‐conventional pricing strategies by clarifying the role of different motivations in consumers' economic decisions, and by identifying contextual factors that trigger or inhibit non‐selfish behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Using experimental data from UK respondents, Vulkan and Shem-Tov (2015) examined this issue and suggested a specific price design to enhance the perception of fairness in the context of personalized pricing: consumers should be asked to pay a fixed percentage (and more specifically, 64%) of their willingness to pay. Many researchers, including Bettray et al (2017) and Richards et al (2016), have found that participative pricing mechanism (paywhat-you-want)consistent with intuitionyielded higher level of fairness sense than ordinary price setting.…”
Section: Loss Aversion Is Stronger In Consumer Durablesmentioning
confidence: 86%
“…This effect is accentuated in online pricing where price comparisons are instantaneous and easy. Further, researchers (Bettray et al, 2017;Richards et al, 2016) have also found that participative pricing mechanism (pay-what-you-want) produced a higher level of fairness and satisfaction. Early research has demonstrated "Fair Pay" pricing architecture and found that the architecture enhances the power of both the buyer and seller [3].…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…Until recently, in the hospitality industry, its application has been quite limited in scope [41,78]. But, nowadays, a combination of factors, including the decline of traditional travel agencies and the rise of online ones, the availability of cheap information and communication technologies and dedicated software have induced many hotels to introduce these practices [15,4,1,7].…”
Section: Introductionmentioning
confidence: 99%